¿Provincias y partidos o gobiernos y corregimientos? Los principios rectores del desordenamiento territorial de las Indias y la creación de un sistema de información histórico-geográfico - Stangl, Werner (Anuario de Historia de América Latina, 2017)
This article deals with the difficulty to reconstruct Spanish American territorial organization of the 18th century for a digital spatio-temporal data-infrastructure (HGIS de las Indias). The observation that it is hard to define Spanish American territorial organization, and that eventually authority was not bundled in one hand and in a well-structured hierarchical system, is hardly novel. However, this article tries to show how administrative, legal, ethnical, historical, and topographical aspects nonetheless worked together forming idiosyncratic, “vernacular” territories labeled reinos, provincias, jurisdicciones, partidos or yet other terms. Perception, definition, and representation of territories and their divisions depended less on a normative system but on stable institutions, regional context, discoursive reproduction, the role/interest of authors, and the medium of expression. Three examples of complicated administrative constellations and their representation in primary sources are treated in more detail: The Frontier of San Luis Colotlán, the province and intendency of Paraguay, and the Kingdom of Nueva Vizcaya. Another part discusses the consequences of such regional realities for a synoptic reconstruction of colonial territory in our historical geographic information system for Bourbon America, HGIS de las Indias. The article is rounded up by general reflections on the applicability of the raised problems to central and marginal areas, a discussion of the scalability of spatial conceptions in texts and maps, and the potential of HGIS de las Indias as common data infrastructure.
Keywords: Territorial Organization; Colonial Administration; Space Production; SIG Histórico; Historical Geography; Colotlan; Paraguay; New Vizcay; Bourbon Reforms